Pelatihan Strategi Pembelajaran Diferensiasi untuk Pengajaran Berkualitas dan Berpusat pada Siswa di Desa Margaluyu - Thahir, Muthahharah; Haerudjaman, R. Haerudjaman; Firdaus, Zaki; Lestari, Esi (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2024)
This service activity aims to support the implementation of differentiated learning in Margaluyu Village, Pangalengan District, Bandung Regency through the Participatory Action Research (PAR) approach. This PAR method involves three main stages: problem identification, material delivery, and evaluation. However, there are challenges in the form of the need for further mentoring and additional training. However, there are challenges in the form of the need for further mentoring and additional training. The results of the activity showed that there was active participation of all parties, showing that the PAR method was effective in encouraging sustainable change. For sustainability, continuous training and mentoring as well as collaboration between schools, communities, and educational institutions are needed.